2, 2-Dimethyl-3, 4-dihydro-2H-1, 4-benzoxazines as isosteres of 2, 2-dimethylchromans acting as inhibitors of insulin release and vascular smooth muscle relaxants. Issue 3 (21st February 2019) - Pirotte, Bernard; Florence, Xavier; Goffin, Eric; Lebrun, Philippe
Abstract : The present study describes the synthesis and biological evaluation of 4-phenylureido/thioureido-substituted 2, 2-dimethyl-3, 4-dihydro-2 H -1, 4-benzoxazines as isosteres of corresponding 2, 2-dimethylchromans reported as KATP channel openers. Abstract : The present study describes the synthesis and biological evaluation of 4-phenylureido/thioureido-substituted 2, 2-dimethyl-3, 4-dihydro-2 H -1, 4-benzoxazines as isosteres of corresponding 2, 2-dimethylchromans reported to be pancreatic β-cell KATP channel openers. The benzoxazines were found to be less active as inhibitors of the glucose-induced insulin release than their corresponding chromans, while the myorelaxant activity of some 4-arylureido-substituted benzoxazines was more pronounced than that exhibited by their chroman counterparts. The myorelaxant activity of the most potent benzoxazine8e was further characterized on rat aortic rings precontracted by 30 mM KCl in the presence of glibenclamide (10 μM) or precontracted by 80 mM extracellular KCl. Our findings indicate that, on vascular smooth muscle cells, the benzoxazine8e mainly behaved as a calcium entry blocker.